The impact of coronavirus disease 2019 on frozen-thawed embryo transfer outcomes - Junrong Diao; Du Aijun; Xinyan Wang; Shuai Zhang; Ying Han; Nan Xiao; Zhe Pang; Junfang Ma; Yunshan Zhang; Haining Luo (PeerJ, 2024)
Background Coronavirus disease 2019 (COVID-19) has raised concerns about its potential effects on human fertility, particularly among individuals undergoing assisted reproductive therapy (ART). However, the impact of COVID-19 on female reproductive and assisted reproductive outcomes is unclear. In this study, we aimed to evaluate the effects of COVID-19 on pregnancy outcomes during frozen-thawed embryo transfer (FET) cycles. Methods This retrospective cohort study included 327 enrolled patients who underwent FET cycles at a single reproductive centre. The study group consisted of patients treated between 1 January 2023 and 31 March 2023 who recently recovered from COVID-19. The embryos for transfer were generated prior to COVID-19 infection. The control group consisted of patients treated between 1 January 2021 and 31 March 2021 who were not infected and did not receive a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine. Demographic and cycle characteristics and outcomes were compared. Results A total of 160 recovered women and 167 controls were included. The primary outcome—the live birth rate—was similar between the two groups (43.8% vs. 43.1%, P > 0.05). The secondary outcomes, such as the implantation rates (41.2% vs. 39.3%), biochemical pregnancy rates (56.3% vs. 56.3%), clinical pregnancy rates (52.5% vs. 52.1%), early abortion rates (8.3% vs. 12.6%) and ongoing pregnancy rates (46.9% vs. 44.3%), were also similar (P < 0.05). According to a logistic regression model, the live birth rate did not decrease after SARS-CoV-2 infection after adjusting for confounding factors (adjusted OR (95% CI) = 0.953 (0.597∼1.523)). Regardless of stratification by age or the number of embryos transferred, the differences remained nonsignificant. Subgroup logistic regression demonstrated that the time interval from infection to transplant had no significant influence on the live birth rate. Conclusions SARS-CoV-2 infection after oocyte retrieval had no detrimental effect on subsequent FET outcomes.